2011
DOI: 10.1262/jrd.10-057t
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Progestagens to Detect and Monitor Pregnancy in Captive Female Cheetahs (Acinonyx jubatus)

Abstract: Abstract. The purposes of the present study were to establish a noninvasive monitoring assay of fecal progestagen measurement to detect pregnancy and to identify the components of fecal progestagens in early, middle and late pregnancy in cheetahs. Feces were collected from 7 female cheetahs and analyzed from 30 days before the last copulation to parturition in 9 pregnancies. Blood was collected from one cheetah. Fecal progestagen and serum progesterone concentrations were determined by enzyme immunoassay (EIA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
8
1
1
Order By: Relevance
“…Conversely, fecal progestogen concentrations reported in this study are far lower than reported by others (Adachi et al, 2011;Brown et al, 1994Brown et al, , 1996Kinoshita et al, 2011). In cheetahs, circulating progesterone is almost completely metabolized and it is excreted in feces mostly as reduced 5-pregnane metabolites; while native progesterone is barely present (Adachi et al, 2011;Brown et al, 1994).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Conversely, fecal progestogen concentrations reported in this study are far lower than reported by others (Adachi et al, 2011;Brown et al, 1994Brown et al, , 1996Kinoshita et al, 2011). In cheetahs, circulating progesterone is almost completely metabolized and it is excreted in feces mostly as reduced 5-pregnane metabolites; while native progesterone is barely present (Adachi et al, 2011;Brown et al, 1994).…”
Section: Discussioncontrasting
confidence: 77%
“…In cheetahs, circulating progesterone is almost completely metabolized and it is excreted in feces mostly as reduced 5-pregnane metabolites; while native progesterone is barely present (Adachi et al, 2011;Brown et al, 1994). The antiserum employed in this study showed poor, if any, cross-reactivity with 5-pregnane metabolites and was not able to detect conjugated progestogens.…”
Section: Discussionmentioning
confidence: 80%
“…There are multiple reports on the independent monitoring of ovarian (Adachi et al, 2011;Brown et al, 1996;Wielebnowski et al, 2002) or adrenal (Crosier et al, 2016;Koester et al, 2015;Terio et al, 2004;Wells et al, 2004) hormone metabolite patterns in the feces of captive-held cheetahs. However, there has been little emphasis on the simultaneous assessment of both metabolites in adult females, especially to determine if measured glucocorticoids are related to estrogen profiles or affect ovarian activity.…”
Section: Introductionmentioning
confidence: 99%
“…When the primordial follicle grows until the stage of de Graff follicle, those hormones are mutually interacted. Previous studies also reported that sexual steroid hormones such as P4, E2, estrone (E1), immunoreactive pregnanediol glucoronide (PdG), estradiol glucoronide (E2G) of female can be used widely to monitor natural ovarian activity such as functional luteal activity and follicular maturation and to confirm pregnancy (Adachi et al 2011;Kusuda et al 2006Kusuda et al , 2007aPutranto 2011c;Putranto et al 2007a, b, c).…”
Section: Introductionmentioning
confidence: 99%